Guanajuato Rumbo al Desarrollo Sustentable, Etapa 2.0: Análisis de bacterias productoras de polihidroxibutirato (PHB) dentro del rol de bioplásticos (JÓVENES EN LA CIENCIA, 2022)
Polyhydroxyalkanoates (PHA) are a class of biodegradable thermoplastic polymers that can be produced from microorganisms. In the PHA family, polyhydroxybutyrate (PHB) is the most studied polymer due to its physical and chemical properties, which are competent against many conventional polymers such as polypropylene (PP). In the present work, the ability of the bacteria Rhodococcus gordoneae, Microbacterium hydrocarbonoxydans, Exiguobacterium indicum and Jeotgalibacillus Soli to produce polyhydroxybutyrate (PHB) from different culture media was studied. Through the Sudan Black staining methodology it was observed that R. gordoneae, Microbacterium hydrocarbonoxydans and Jeotgalibacillus Soli showed a positive production for PHB. These results contribute to biotechnological research into sustainable development for the use of biodegradable plastics from microorganisms.